2006
DOI: 10.1191/0960327105ht626oa
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Ziziphora clinopoides of acetic acid-induced toxic bowel inflammation through reduction of cellular lipid peroxidation and myeloperoxidase activity

Abstract: Inflammatory bowel disease (IBD) is a chronic condition of the intestine with unknown etiology involving multiple immune, genetic and environmental factors. We were interested in examining the effect of a total extract from Ziziphora clinopoides, an Iranian folk herbal medicine, in the prevention and control of experimental mouse IBD. Z. clinopoides was administered (75, 150, 300 mg/kg) through drinking water to mice, which dispensed a toxic dose of acetic acid intrarectally. Prednisolone was used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 51 publications
(6 reference statements)
1
32
0
Order By: Relevance
“…It has been suggested that control of oxidative stress in IBD may attenuate biochemical and histopathological variables of IBD [8][9][10][11]. In this regard, existence of oxidative stress in biological fluids such as saliva [12], plasma [13], and colonic mucosal biopsies [2] of subjects with IBD has been already confirmed.…”
Section: Introductionmentioning
confidence: 83%
“…It has been suggested that control of oxidative stress in IBD may attenuate biochemical and histopathological variables of IBD [8][9][10][11]. In this regard, existence of oxidative stress in biological fluids such as saliva [12], plasma [13], and colonic mucosal biopsies [2] of subjects with IBD has been already confirmed.…”
Section: Introductionmentioning
confidence: 83%
“…Tissue MPO activity, a marker of neutrophil sequestration and infiltration into GI tract, has been used extensively as a biomarker of inflammation [7][8][9]. This marker is stored in some immune cells, such as neutrophils, and is responsible for mediating microbial killing as well as initiation and progression of both acute and chronic inflammatory reactions [48].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the use of complementary and alternative therapies is also common in 50% of patients suffering from IBD [6]. Moreover, various herbal extracts [7][8][9][10], N-acetylcysteine (NAC) [11] and probiotics [12][13][14][15] have been suggested for the treatment of IBD, and the effectiveness of antibiotic therapy in IBD has been investigated [16,17]. Unfortunately, it is very difficult to reach maximum efficacy and quality of life because of the side effects [18] associated with the treatments described above.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there are numerous studies on the antioxidant potential of Thymus species growing in various regions of the world (Ismaili et al, 2004;Sokmen et al, 2004;Agbor et al, 2005;Ozgen et al, 2006;Vitalini et al, 2006). Recent reports show that various Thymus and several Ziziphora species have antioxidant potential (Ismaili et al, 2004;Sokmen et al, 2004;Agbor et al, 2005;Salehi et al, 2005;Ghafari et al, 2006;Ozgen et al, 2006;Vitalini et al, 2006). As shown in Figures 1 and 7, all extracts of Z. clinopodioides and T. fallax have potent antioxidant and free radical scavenging activities.…”
Section: Antioxidant and Dpph Radical Scavenging Activities Of The Exmentioning
confidence: 99%